Brachyspira hyodysenteriae - Carlertz, Anna (2016)
Swine dysentery is caused by the spirochaete Brachyspira (B.) hyodysenteriae that is a severe and expensive disease, primarily affecting slaughter pigs. When a herd gets infected for the first time, the mortality rate can reach high levels. In herds where the disease has become chronic, a reduced weight gain might be the most prominent sign. The disease has a great impact on the animal welfare, it is expensive for the owners, and causes an increased use of antibiotics. In many European countries, although not in Sweden, B. hyodysenteriae has developed resistance towards some of the most commonly used antibiotics. In 1996, a project started to reduce the prevalence of swine dysentery in Sweden. During the following ten years, the numbers of infected herds decreased tremendously. The positive development thereafter seemed to stagnate. During the last five years, the annual frequency rate of samples submitted to SVA (National Veterinary Institute) obtaining a positive result has been on a consistent level. The purpose of the project has been to survey the existence of B. hyodysenteriae in Swedish pig herds regarding the number of positive herds, geographic location and genetic diversity of species. The plan was to use the result in a future eradication programme. The project was divided in two parts. One part was a survey on potential relationships between the positive lab samples obtained, for which the RAPD fingerprinting method was used. The second part of the project was a questionnaire sent to Swedish pig health veterinarians. The veterinarians were asked to answer questions about the present situation of swine dysentery, how they managed infected herds and if they had been successful. The answering veterinarians were also contacted by phone for additional questions.